Political economy of redistribution between traditional and modern families - Volker Meier; Matthew D. Rablen (Center for Economic Studies and ifo Institute (CESifo), 2019)
We analyse a model in which families may either be “traditional” single-earner with caring for the child at home or “modern” double-earner households using market child care. Family policies may favour either the one or the other group, like market care subsidies vs. cash for care. Policies are determined by probabilistic voting, where allocative and distributional impacts matter, both within and across groups. Due to its impact on intragroup distribution, both types of households are likely to receive subsidies. In early stages of development where most households are traditional, implemented policies favour them, though to a small extent. Net subsidies to traditional households are highest in some intermediate stage, which may explain the implementation of cash for care policies. Such policies will be tightened again in late stages of development, where the vast majority of voters come from modern households. Finally, in an environment in which many traditional households are not entitled to vote (immigrants who have not yet obtained citizenship), redistribution toward them may be abolished and in extreme cases even replaced by net transfers to modern households.
Keywords: D13; H21; J13; J18; J22; 330; redistribution; child care; subsidies; family policy; labour supply